Recuperaç\~ao econômica e fechamento gradual do hiato: Um exercício de consistência de médio e longo prazos - José Ronaldo de Castro Souza; Fabio Giambiagi (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– This article discusses which may be the trajectory of the Brazilian economy over the 2020s, particularly in the transition from the current period when there is idle capacity in the economy to a period when the growth of supply capacity may again be crucial for growth. From the context created by the recession of 2020 caused by the coronavirus pandemic - which resulted in the expansion of the output gap - and a discussion of the limitations that will condition the future performance of the economy, we show the scenario outlined, explaining its logic, the determinants and the assumptions. That said, we explain why the pattern of potential GDP recovery expected in the coming years differs from that seen on previous occasions. The fi gures suggest that Brazil will have a modest expansion of potential GDP at the beginning of the projection, however, that the growth of the variable can be accelerated gradually with the gradual increase in the investment rate and productivity growth. Despite the low potential GDP initial growth, the degree of idleness would allow an average GDP growth of around 2.5% pa between the base year of 2021 and the end of the decade - considering the scenario proposed in the article. In this scenario, the country would reach the end of the decade with an investment rate of more than 22% of GDP. Thus, if the country manages to face the challenges of fi scal consolidation and the implementation of reforms that improve productivity and attract private investment, the prospects for the decade would be very promising, after the extremely negative decade of 2010/2020.
Keywords: E22; E24; E32; E37; O47; 330; potential output; output gap; economic growth; productivity; growth scenarios